ANALISIS POTENSI PENDIRIAN DAN PENGELOLAAN BUMDES DI WILAYAH KECAMATAN SAGALAHERANG KABUPATEN SUBANG - Endang Irawan Supriyadi (Universitas Muhammadiyah Sumatera Utara, 2023)
BUMDes is a business entity legalized by the government with the main objective of building a business in accordance with the potential of the village for the greatest possible welfare of the village community, although there are still obstacles encountered empirically. Therefore this study will analyze the potential and obstacles encountered in establishing BUMDes in the Sagalaherang District, Subang Regency. This research method uses a Qualitative Research Method with a Case Study approach. The results of this study using SWOT analysis show that BUMDes in the Sagalaherang District, Subang Regency have potential that can be utilized, where Sagalaherang District is included in the Tourism area and even several villages have received a Regent's Decree as a Tourism Village but have limitations regarding human resources managing BUMDes besides that the community and administrators still don't understand the purpose of establishing BUMDes. Therefore it is necessary to socialize BUMDes to the community and implement the development of BUMDes management human resources